Analysis of the tourist offer of the city of Zagreb: A tourist perspective - Alkier-Tomić Romina; Milojica Vedran; Vučenović Danijel (Ekonomski Pogledi)
The paper emphasizes the importance of city tourism as a specific form of tourism with the modern tourist offer, and presents the attitudes of tourists who visited the city of Zagreb for their holiday. The authors analyzed the most current scientific findings on this topic, as well as the selected findings of the most recent study Attitudes and Expenditures of Tourists in Croatia TOMAS 2022/23. Results presenting their motives and preferred activities indicate the possibility of insufficient recognizability of elements of tourist offer by the tourists, which might have resulted in lower interest in trying certain activities. In terms of satisfaction, tourists are mostly satisfied with the elements of Zagreb tourist offer, however, it is necessary to improve the quality of the information provided about the destination, Internet access, and marketing activities. Based on the findings the authors discussed the developmental guidelines.